Peran Pembelajaran PPKn dalam Membentuk Etika dan Moral Peserta Didik di Lingkungan Sekolah - Fatiani Lase (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe the role of Citizenship Education, the challenges encountered, and the efforts undertaken in shaping the ethics and morals of students at SMA Negeri 1 Lahewa. The research employs a qualitative approach with a descriptive method. Data sources were obtained through observation, in‑depth interviews with the principal, teachers, and students, as well as documentation. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that Citizenship Education serves as the primary medium for instilling noble values, although its implementation has not yet been fully optimal due to the existing gap between knowledge and behavioral application. The challenges faced include students’ perceptions, limitations in teaching methods, external environmental influences, and consistency in enforcing school rules. Efforts made consist of improving teaching approaches, integrating values into all school activities, enforcing discipline, and setting good examples by all school members. This study concludes that the role of Citizenship Education can function optimally if supported by appropriate methods, a conducive environment, and cooperation from all parties within the school.